(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
Social contracts theory holds that evolutionary mechanisms and adaptative rules regulate social exchanges. In this paper, we analyze two experiments that this theory has presented for supporting its hypotheses. After such a review, we conclude that fundamental suppositions of social contracts theory are not demonstrated and that its experimental outcomes can be explained from formal classic logic.